Problem-based learning in communication systems using MATLAB and simulink - Choi, Kwonhue; Liu, Huaping (IEEE Press., 2016)
Designed to help teach and understand communication systems using a classroom-tested, active learning approach.- Resumé vydavatel
Keywords: MATLAB.; SIMULINK.; bezdrátové komunikační technologie; telekomunikační technika; počítačová simulace; MATLAB (software); SIMULINK (software); wireless communication technology; telecommunications technology; computer simulation; elektronické knihy; sborníky; electronic books; papers of several authors